Implementasi Pembelajaran PBL Berbasis Kearifan Lokal pada Alat Musik Tradisional NTT Materi Gelombang untuk Meningkatkan Hasil Belajar Siswa SMP - Teuf, Petronela Juliesti; Marlince Dopong; Grace Victoria Labeul; Hilary Fridolin Lipikuni; Yanti Boimau; Wenti Marlensi Maubana; Angelikus Olla (Program Studi Fisika - Universitas San Pedro, 2026)
The Problem-Based Learning (PBL) model is a teaching paradigm that facilitates the development of critical thinking skills. Local wisdom refers to a way of life and knowledge manifested in activities commonly practiced by the wider community in a particular region. One example of local wisdom can be traditional musical instruments, which can be incorporated into the learning model. Combining the PBL learning model with local wisdom can help students who struggle to understand conceptual materials, particularly in science education. Integrating local wisdom into science learning can enhance students' understanding. This study aims to improve students' learning outcomes using PBL-based learning grounded in local wisdom on physics topics such as vibrations, waves, and sound for eighth-grade students at SMP Reformasi Plus. The research method used in this study is The experimental method with research subjects consisted of 38 eighth-grade students divided into two classes: VIII-A as the experimental class and VIII-B as the control class. The learning outcomes from the implementation of PBL learning based on local wisdom showed that the N-Gain pretest score for the experimental class was 0.53 and for the control class was 0.49, which falls into the moderate category. Meanwhile, the posttest score for the experimental class was 0.82 and for the control class was 0.67, which falls into the high category. These results indicate that there is an effect of applying the PBL learning model based on local wisdom on improving students' learning outcomes.